GameFY: criação de um sistema gamificado com inteligência artificial - Quiroz, Victor Bruno Alexander Rosetti de (2023)
This work studied and was the basis for the creation of a content gamification platform that, through artificial intelligence, is able to analyze how higher education students learn programming. The research worked on the areas of machine learning, in order to create an AI model for each user, and on learning analytics, in order to understand how the user learns. These areas are worked on along with content gamification, listing various types of activities so that the student can be tested and instigated. To make the research more robust, systems that are already on the market are analyzed to find out the best ways to captivate students. It was not possible to complete the system so that it would be available to the public, but it was possible to use and partially test it. However, the way to complete the system is clear and well grounded, allowing the finalization of the system in future works